Is front crawl swimming performance affected by hydrodynamic drag in young swimmers? - Silva, A.J. (2010)
Swimming performance is affected by several factors including the hydrodynamic drag. Hydrodynamic drag is the force that a swimmer has to overcome in order to maintain his movement through water and is highly dependent on swimming technique. PURPOSE: To analyse in young swimmers the relationship between hydrodynamic drag and the front crawl performance. METHODS: 25 young swimmers (11 females and 14 males) participated in this study. Their mean (standard deviation) age, body mass, height and best swimming performance in 100 m front crawl was 12.08 (0.76) years, 43.08 (7.60) kg, 1.52 (0.08) m and, 75.11 (9.57) s, respectively